PENGARUH KUALITAS PELAYANAN PASTRY SECTION TERHADAP MINAT BELI TAMU DI SINTESA PENINSULA HOTEL - Sendow, Jelly; Martini, Sri; Ando, Aurellio X. L. (Jurnal Hospitaliti, 2023)
This study aims to determine the Effect of Pastry Section Service Quality on Guest Buying Interest at Sintesa Peninsula Hotel Manado. The research method used is the Quantitative Method, with data analysis techniques Simple Linear Regression. The population in this study were hotel guests, with a sample of sixty guests at the Sintesa Peninsula Hotel Manado. The results of the study prove that the Pastry Section Service Quality has a positive and significant effect on Guest Buying Interest with an F-count value of 53.975 and a significance of 0.000. This shows that the better the quality of service, the more guests' buying interest will increase. The conclusion of this study is the quality of service and has a significant influence on the Buying Interest of Guests at Sintesa Peninsula Hotel Manado. The advice given is that Sintesa Peninsula Hotel Manado maintains or improves the quality of its services so that guests have a high buying interest in the services that have been provided, and always update and arrange facilities at Sintesa Peninsula Hotel Manado.